PERSEPSI ANAK USIA SEKOLAH TERHADAP KESEHATAN DIRI DAN UPAYA PHBS DI KABUPATEN BOYOLALI - Kristiawan Prasetyo Agung Nugroho; Septiana Dian Anggraheni (MEDIA ILMU KESEHATAN, 2017)
Background:There are still many incidents of school-age illness (6-14 years) that occur repeatedly over time because the child has not realized the importance of maintaining a healthy lifestyle for himself. Bad behavior habits in children will have an impact on efforts to maintain a healthy lifestyle. Objective: To know the perception of children about their health and healthy life behavior that can be done, so as to prevent the incidence of recurrent illness that is often suffered by school-aged children, and become the impetus to make healthy lifestyles include children's perception of disease, behavior, and knowledge on health . Methods: Qualitative research with primary data collection techniques and secondary data. Respondents were 23 students of grade IV and V elementary school in Boyolali Regency who were chosen by purposive sampling according to inclusion and exclusion criteria. Results: Types of diseases that are often suffered by the respondents are disturbances of the digestive system, respiratory, urinary, and nervous system. Habitual things that are still done by respondents are buying unclean and unhealthy foods. Most of the respondents are still doing some physical movement activities done at school and at home by doing sports. Conclusions: The respondents are able to identify some of the diseases that have been experienced and the cause of the disease he suffered. The respondents are also able to explain the understanding of health and efforts to maintain health according to the knowledge they have, and be able to mention the criteria of healthy food, explain the behavior of clean living to be done, and apply the pattern of adequate rest. Keyword: Perception of health, school aged-children, personal health problem